Potential Negative Effects of Dextromethorphan as an Add-On Therapy to Methylphenidate in Children With ADHD - Chuang, Wei-Chen; Yeh, Chin-Bin; Wang, Sheng-Chiang; Pan, Pei-Yin; Shyu, Jia-Fwu; Liu, Yia-Ping; Gau, Susan Shur-Fen; Lu, Ru-Band (Frontiers in Psychiatry, 2019)
Objectives: Methylphenidate (MPH) is highly effective in controlling the symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD), but some children with ADHD either do not respond to, or do not tolerate treatment. Dextromethorphan (DM) is a neuroprotective agent which has been used in the treatment of neuropsychiatric disorders. This clinical trial had examined the effect of DM on the use of MPH in the children with ADHD. Methods: This randomized double-blind clinical trial had evaluated 44 male outpatients, aged between 6 and 12 years, with a diagnosis of ADHD. The study subjects were randomly assigned into one of the two groups: receiving MPH alone (15-60 mg per day) or MPH plus DM (30-60 mg per day) for 8 weeks. Assessments, comprising the Chinese version of the Child Behavior Checklist (CBCL-C) scale and the Swanson, Nolan and Pelham Questionnaire (SNAP)-IV rating tests conducted by parents and the serum cytokines measured by microarray and ELISA, were compared between groups at baseline and at 8 weeks after the medication was started. Results: There were a significant decrease at the mean scores of both CBCL-C and SNAP-IV scales after 8 weeks treatment, but no significant differences between MPH and MPH+DM groups had found regarding the pattern of changes had observed. Compared to the MPH-only group, the mean scores of some psychometric parameters reported on the CBCL-C and SNAP-IV scales regarding Time effects as well as the attention problems on the CBCL-C scale regarding Group effect were significantly higher in the DM+MPH group. Although there were no significant differences in the levels of various serum cytokines between groups, the subjects in the DM-MPH group had relatively fewer and lower levels of adverse effects. Significant interactions were found between the withdrawn/depression item reported on the CBCL-C scale and TNF-α (p=0.027), as well as between thought problems item on the CBCL-C and TNF-α (p=0.028) in subjects who had received DM+MPH treatment . Conclusion: Following the trial, DM+MPH was not superior to MPH alone for the treatment of children with ADHD, yet DM may potentially have negative effects on ADHD symptoms when combined with MPH.